Application of urea based SNCR system in the combustion effluent containing low level of baseline nitric oxide - Hossain, K. A.; Mohd. Jaafar, M. N.; Appalanide, K. B.; Mustafa, A.; Ani, F. N. (Taylor and Francis Ltd, 2005)
Selective Non-Catalytic Reduction (SNCR) of nitric oxide has been studied experimentally by injecting aqueous urea solution with and without additive in a pilot-scale diesel fired tunnel furnace at 3.4% excess oxygen level and with low ppm of baseline NO(x) ranging from 65 to 75 ppm within the investigated temperature range. The tests have been carried out using commercial grade urea as NO(x) reducing agent and commercial grade sodium carbonate as additive. The furnace simulated the small-scale combustion systems, where the operating temperatures are usually in the range of about 973 to 1323 K and NO(x) emission level remains below 100 ppm. With 5% plain urea solution, at Normalized Stoichiometric Ratio (NSR) of 4 as much as 54% reduction was achieved at 1128 K, whilst in the additive case the NO(x) reduction was improved to as much as 69% at 1093 K. Apart from this improvement, in the additive case, the effective temperature window as well as peak temperature of NO(x) reduction shifted towards lower temperatures. The result is quite significant, especially for this investigated level of baseline NO(x). The ammonia slip measurements showed that in both cases the slip was below 16 ppm at NSR of 4 and optimum temperature of NO(x) reduction. Finally, the investigations demonstrated that urea based SNCR is quite applicable to small-scale combustion applications and commercial grade sodium carbonate is a potential additive.